Analysis of the Influence of Motivation on Service Quality and Staff Performance in the Emergency Department - Muhammad Al-Fhitrah Lakidende (Newinera Publisher, 2026)
The performance of Emergency Department (ED) personnel constitutes a critical determinant of hospital service quality. This study aims to analyze the influence of work motivation on service quality and staff performance, as well as the effect of service quality on staff performance at the Emergency Department of Lakipadada Regional Hospital, Tana Toraja, while identifying the most dominant factor affecting staff performance. The research employed a quantitative approach with an analytical design. The sample comprised 50 ED personnel selected through total sampling. Data were collected using structured questionnaires and analyzed through multiple linear regression, including t-tests, F-tests, and the coefficient of determination (R²). The findings indicate that work motivation has a significant effect on service quality (β = 0.393; p = 0.005). Partially, both work motivation (β = 0.393; p = 0.005) and service quality (β = 0.479; p = 0.001) significantly influence ED staff performance. Simultaneously, work motivation and service quality significantly affect staff performance (F = 49.521; p = 0.001). The coefficient of determination reveals that 67.8% of the variance in staff performance can be explained by work motivation and service quality (R² = 0.678), with service quality emerging as the most dominant factor. These findings underscore the necessity of managerial strategies focused on enhancing both work motivation and service quality to improve the performance of ED personnel at Lakipadada Regional Hospital, Tana Toraja.